#Democracy: social media use and democratic legitimacy in Central and Eastern Europe. Issue 4 (7th June 2017) - Placek, Matthew Alan
ABSTRACT: Since 1989, many of the former communist countries in Central and Eastern Europe (CEE) have made the dramatic change from communist regimes to democratic nations that are integrated in the European sphere. While these sweeping changes have given rise to a successful transition to democracy unlike any the world has ever seen, there remain issues with governance as well as citizen support for the regime. While other studies have shown that mass media can influence a person's attitudes and opinions in the region, none has explored what effect social media can have on orientations toward democracy in the region. In the following paper, I build several hypotheses based on previous studies of media effects and democratic survival. I then employ survey data to empirically test whether social media increases support for democracy. The study finds that not only does using social media increase support for democracy, but also simple usage rather than information seeking provides more consistent effects on a person's support for democracy in CEE.